Can ICT investment promote green development? new insights from highly polluting listed enterprises in China. - Yingdong Wang; Qingbo Li (PLoS ONE)
Green development is related to the long-term sustainable development of enterprises, but there is little literature on the impact of information and communication technology (ICT) investment on green development of enterprises. To fill this gap, based on the sample of A-share high-polluting industry enterprises in China's Shanghai and Shenzhen stock markets from 2007 to 2019, this paper uses the dynamic panel threshold model to deeply study the non-linear impact of ICT investment on green development. This paper found that: (1) there is a threshold effect on the impact of ICT investment on green development of enterprises in high-polluting industries, and when ICT investment breaks through the threshold value, it can promote green development. This conclusion remains robust after the estimation of Multi-period DID model and instrumental variable; (2) ICT investment mainly promotes green development of enterprises by improving production efficiency and promoting green technology innovation; (3) ICT investment has a significant impact on green development of enterprises with higher management level, heavy industrial enterprises and non-state-owned enterprises, but has no significant impact on green development of enterprises with lower management level, light industrial enterprises and state-owned enterprises. And digital technology investment has a stronger role in promoting green development than traditional ICT investment. This paper proposes that enterprises in high-pollution industries can increase ICT investment to promote green development.